Estimación de los servicios ecosistémicos de regulación (captura de carbono) en los Parques de la Ciudad de Latacunga. - Reino Choto, Diego Xavier (2019)
This research had as main aim the aerial biomass estimation and carbon capture capacity from Vicente León, Filantropia and La Laguna tree species parks at Latacunga city. These estimative indicators are elements of great importance to consider in order to establish the state of the natural and urban ecosystems and their contribution to the reduction of the carbon dioxide concentration in the cities. This was done through the identification of the existing tree species in the researched sites where data was collected in order to obtain concrete results about the species found in these. The study area of the three parks is 43318.04m2. Where it was done a quantification of the tree species having a total of 203 trees with 8 different species between native and introduced. It was observed that trees with a smaller diameter produce little biomass, therefore, the carbon fixation is directly proportional. For this reason, only data from 132 trees were taken. The height of the tree, the diameter at breast height (DBH), and age must be measured in order to get valid data. In addition, it is used aerial biomass collectors manufactured with a diameter of 1.20m, a height of 0.5m and these were installed 1m above the ground. The result of the biomass in the Vicente León park was 13.74t/ha, in Filantropia 16.26t/ha, and La Laguna 34.15t/ha. Regarding the indicator of carbon capture in all three study areas, it was 32.075t/ha. With these results, the highest percentage of carbon content of the parks was of La Laguna, with 17.075t/ha/month which represents the 53% of the total carbon content of the three parks analyzed. This is due to the fact that in that place there is a greater diversity of species and to dominate the native ones. It represents favorable data which let to know that the species that help most in capturing carbon are native species such as Molle with 7.82t/ha and Yagual with 3.34t/ha. Because of these results, there is a clear vision towards an effective urban reforestation program.